CHARACTERIZATION OF MECHANICAL PROPERTIES AND BIODEGRADABILITY OF BANANA PEEL STARCH-BASED BIOPLASTICS (Musa paradisiaca) WITH GLYCEROL–SORBITOL AND CHITOSAN - Metta Wijayanti; Putri Febrianti; Desti Lidya (KINETIKA, 2025)
Biodegradable plastic is plastic that is easily decomposed by microorganisms. Biodegradation of plastic can be achieved by activating microorganisms in the environment to metabolize the molecular structure of plastic films. The benefit of this research is to address the problem of plastic waste in the surrounding environment into environmentally friendly plastic packaging by utilizing banana peel starch waste. The use of starch as the main ingredient in plastic production has great potential because in Indonesia there are various starch-producing plants. In this study, banana peel starch was used as a raw material, sorbitol as a plasticizer, and chitosan as a filler in the production of biodegradable plastic. The purpose of this study was to determine the mechanical properties of the obtained biodegradable plastic, such as tensile strength, elongation, water resistance, and biodegradability. The materials used in this study have different composition variations, namely 5 grams of banana peel starch using 50 ml of distilled water, 3 ml of Acetic Acid (1%) and Plasticizer in the form of Glycerol and Sorbitol with variations (20%:0%), (15%:5%), (10%:10%), (5%:15%), (0%:20%) and variations of Chitosan 2% and 4%. The best analysis results of bioplastics obtained were with variations of glycerol, sorbitol 0:20, and chitosan 2% obtained tensile strength values of 1.751Mpa, elongation 43%, water resistance 82.50%, and biodegradation 79.76%. Some bioplastic samples have met the SNI 7188.7:2016 standard.